Regional moderate hyperthermia for mild-to-moderate COVID-19 (TherMoCoV study): a randomized controlled trial - Mancilla-Galindo, Javier; Kammar-García, Ashuin; Mendoza-Gertrudis, María de Lourdes; García Acosta, Javier Michael; Nava Serrano, Yanira Saralee; Santiago, Oscar; Torres Vásquez, Miriam Berenice; Martínez Martínez, Daniela; Fernández-Urrutia, Liliana Aline; Robledo Pascual, Julio César; Narváez Morales, Iván Daniel; Velasco-Medina, Andrea Aida; et al. (Frontiers in Medicine, 2023)
Background To prevent COVID-19 progression, low-cost alternatives that are available to all patients are needed. Diverse forms of thermotherapy have been proposed to prevent progression to severe/critical COVID-19. Objective The aim of this study is to evaluate the efficacy and safety of local thermotherapy to prevent disease progression in hospitalized adult patients with mild-to-moderate COVID-19. Methods A multicenter, open-label, parallel-group, randomized, adaptive trial is used to evaluate the efficacy and safety of local thermotherapy to prevent disease progression in hospitalized adult patients with mild-to-moderate COVID-19. Eligible hospitalized adult patients with symptoms of COVID-19 with ≤5 days from symptom onset, meeting criteria for mild or moderate COVID-19, were randomly assigned to the intervention consisting of local thermotherapy via an electric heat pad in the thorax (target temperature range 39.5–42°C) continuously for 90 min, twice daily, for 5 days, or standard care. The main outcome was the proportion of patients who progressed to severe-to-critical COVID-19 or death. Patients were randomized in a 1:1 ratio through a centralized computer-generated sequence of minimization with a random component of 20%. Participants and medical staff were not blinded to the intervention. Results One-hundred and five participants (thermotherapy n = 54, control n = 51) with a median age of 53 (IQR: 41–64) years were included for analysis after the early cessation of recruitment due to the closure of all temporal COVID-19 units (target sample size = 274). The primary outcome of disease progression occurred in 31.4% (16/51) of patients in the control group vs. 25.9% (14/54) of those receiving thermotherapy (risk difference = 5.5%; 95%CI: −11.8–22.7, p = 0.54). Thermotherapy was well tolerated with a median total duration of thermotherapy of 900 (IQR: 877.5–900) min. Seven (13.7%) patients in the control group and seven (12.9%) in the thermotherapy group had at least one AE (p = 0.9), none of which were causally attributed to the intervention. No statistically significant differences in serum cytokines (IL-1β, IL-6, IL-8, IL-10, IL-17, and IFN-γ) were observed between day 5 and baseline among groups. Conclusion Local thermotherapy was safe and well-tolerated. A non-statistically significant lower proportion of patients who experienced disease progression was found in the thermotherapy group compared to standard care. Local thermotherapy could be further studied as a strategy to prevent disease progression in ambulatory settings. Clinical Trial registration: www.clinicaltrials.gov, identifier: NCT04363541.